Comparison of parameters of gamma ray sources and laser sources for calculating a prescribed radiation dose for the treatment of cervical cancer at a low dose rate using the Monte Carlo code MCNP (Damascus University Journal for engineering sciences, 2022)
In this paper, a comparison was made between the parameters of the gamma ray sources and a pulsed laser source in the visible and infrared spectrum (600-1100) nm to calculate a prescribed radiation dose for a patient in the case of cervical cancer treatment at a low dose rate using the Monte Carlo code MCNP.The results of the calculation indicated that:- The laser source is able to give the same value as the absorbed radiation dose prescribed to the patient for the treatment of cervical cancer by contact, which amounted to (14-16) Gy,- The treatment time of the patient using a laser absorbed dose was (6.7) minutes, and this time is much less than that in the case of using radioactive sources of gamma, which amounted to (18) hours,- The laser absorbed dose in the organs surrounding the uterus is much lower than in the case of using gamma radioactive sources, which spares healthy tissues the risks of exposure to ionizing radiation.
Keywords: Cervical cancer; gamma rays; laser; phantom MIRD5; MCNP code